2007
DOI: 10.1093/molbev/msm204
|View full text |Cite
|
Sign up to set email alerts
|

Multicopy Suppression Underpins Metabolic Evolvability

Abstract: Our understanding of the origins of new metabolic functions is based upon anecdotal genetic and biochemical evidence. Some auxotrophies can be suppressed by overexpressing substrate-ambiguous enzymes (i.e., those that catalyze the same chemical transformation on different substrates). Other enzymes exhibit weak but detectable catalytic promiscuity in vitro (i.e., they catalyze different transformations on similar substrates). Cells adapt to novel environments through the evolution of these secondary activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
179
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(192 citation statements)
references
References 45 publications
10
179
2
1
Order By: Relevance
“…Hits were obtained from every class of toxic compound tested ( Table 1). The hit rate (resistance to 36% of all toxins) was even higher than in our previous study (23), where only 20% of single-gene knockout strains were rescued by noncognate ASKA ORFs. As hypothesized previously (38), we have shown that a bacterium from a nonclinical environment (in this case, a laboratory strain of E. coli) can nevertheless possess a significant reservoir of latent resistance determinants.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Hits were obtained from every class of toxic compound tested ( Table 1). The hit rate (resistance to 36% of all toxins) was even higher than in our previous study (23), where only 20% of single-gene knockout strains were rescued by noncognate ASKA ORFs. As hypothesized previously (38), we have shown that a bacterium from a nonclinical environment (in this case, a laboratory strain of E. coli) can nevertheless possess a significant reservoir of latent resistance determinants.…”
Section: Discussioncontrasting
confidence: 61%
“…To avoid this source of bias, we used a significantly lower concentration of IPTG (50 μM) to induce protein expression. This amount is sufficient for derepression of the pCA24N T5-lacO promoter, but minimizes fitness differences associated with overexpression of different ORFs (20,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study, as well as a similar study by Patrick et al (23), fills an important gap and comprehensively shows that multifunctionality and promiscuity in proteins are common and that gene overexpression can allow access to this reservoir of new activities. The multicopy suppression approach provides a powerful methodology to access this reservoir, and it is likely to be an important future tool to define the "promiscuome" in various organisms.…”
Section: Evolution Of New Genessupporting
confidence: 71%
“…This suggestion can be tested both genetically and biochemically. The genetic studies were first reported by Patrick et al (17), who conducted a large-scale study to test whether chromosomal deletions of single genes in E. coli could be rescued by other E. coli genes overexpressed from a plasmid. In the case of the ΔserB auxotroph, Patrick et al (17) found that overexpression of HisB rescued the deletion.…”
Section: Histidinol Phosphate Phosphatase Encoded By Hisb Is Promiscuousmentioning
confidence: 99%